(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background: Teachers’ knowledge towards childhood mental health disorders at schools located in regions which were exposed to armed conflict, traumatic events and wars should be given the highest priority, not only for pupils’ mental health, but also as an important perspective for education. Therefore, teachers’ knowledge must be adequately assessed about common childhood mental health disorders, particularly posttraumatic stress disorder (PTSD). Objectives: The study aimed to assess teachers’ knowledge towards post-traumatic stress disorder (PTSD) among pupils at primary schools in Mosul city. Materials and Method: A descriptive study was conducted for the period from 1st December 2018 to 30th May 2019. The study included (520) primary schools inside Mosul which is the second largest city in Iraq. A probability sampling (simple random technique) was used, the sample consisted of (60) teachers who were teaching in primary schools inside Mosul city. Data were collected through the utilization of constructed questionnaire after validity and reliability of it were estimated. Reliability of the questionnaire was estimated through a pilot study and the validity was determined through(15) experts related to the field of study. All data were collected by means of interview technique. Data were analyzed through use of descriptive and inferential statistical analysis procedures using SPSS Version-23. Results: The findings of current study indicates that the level of teachers’ knowledge towards post-traumatic stress disorder (PTSD) was low. Conclusion: The study concludes that there is a considerable lack in teachers’ knowledge in regard to posttraumatic stress disorder (PTSD).